Intelligent Distributed Computing IV Proceedings of the 4th International Symposium on Intelligent Distributed Computing - IDC 2010, Tangier, Morocco, September 2010 - Essaaidi, Mohammad; Maugeri, Michele; Badica, Costin (Studies in Computational Intelligence,, 2010)
This book represents the combined peer-reviewed proceedings of the Fourth International Symposium on Intelligent Distributed Computing -- IDC 2010 and of the Second International Workshop on Multi-Agent Systems Technology and Semantics -- MASTS'2010. Both events were held in Tangier, Morocco during September 16-18, 2010. The 33 contributions published in this book address many topics related to theory and applications of intelligent distributed computing and multi-agent systems, including: agent-based e-business, ambient intelligence, bio-informatics, collaborative systems, cryptography and security, distributed algorithms, distributed data mining, distributed simulation, grid computing, image processing, information extraction, knowledge management, logic programming, mobile agents, ontologies, pervasive computing, Petri nets, process modeling, self-organizing systems, semantic web services, service oriented computing, social networks and trust, swarm intelligence, web applications, wireless sensor networks.